The Effect of Artificial Intelligence in terms of Effectiveness and Efficiency on Military Operation - Fachry Fachraddin Rahman; Fauzia Gustarina Cempaka Timur; I Wayan Midhio (Kemudi, 2025)
This research explores the impact of implementing artificial intelligence (AI) on the effective-ness and efficiency of military operations. With rapid technological advancements, AI has be-come a crucial component in the modernization of military strategy and tactics. This research describes the impact of artificial intelligence on military operations in terms of effectiveness and efficiency. The methodology is descriptive qualitative research on how AI affects military operations and how it compares before the influence of AI. The results show that AI can signif-icantly improve operational effectiveness by increasing intelligence accuracy and tactical re-sponsiveness, as well as efficiency by reducing operational costs and increasing decision-making speed. However, the research also identified associated challenges and risks, such as cybersecurity concerns and the ethics of using AI in armed conflict. The findings provide valu-able insights for military decision-makers and technology developers in designing optimal AI integration strategies.